STRUKTUR DAN KOMPOSISI GASTRPODA DI PADANG LAMUN PADA PERAIRAN PANTAI LANERE DESA BATUAWU KABUPATEN BOMBANA SULAWESI TENGGARA - Jamili Jamili; Muhsin Muhsin; Nafilah Nafilah (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2015)
ABSTRACT The aim of this study was to know the structure and composition of gastropods in seagrass beds in Coastal Waters Lanere Batuawu Village District of South Kabaena. This study was conducted in April to June 2014.The population of this study are all individuals of each type of gastropods were to be found in the study area, the sample of this study is the whole individual types of gastropods contained in the observation plots. The method used in this study was The Line Transect with the placement of plots semi subjective based on the condition of seagrass. The observations were made on 5 transects. The distance between transects were 50 and each transects contains 10 plots.The structure and composition was analyzed quantitatively by determining density, relative density, frequency, relative frequency, Important Value Index, Diversity Index (H), and Evenness Index (E). The result of this study showed that found 27 species of gastropods in whole transects. The Shannon-Wienner estimated index was 1,360 to 1,924 and The Evennes Index was 0,494 to 0,583. Important Value Index highest gastropods were Hebra corticata, Nassarius coronatus and Plicarcularia thersites. Keywords : Gastropods, Structure, Composition, Diversity, Evenness, Seagrass